Understanding LrgAB Regulation of Streptococcus mutans Metabolism - Ahn, Sang-Joon; Hull, William; Desai, Shailja; Rice, Kelly C.; Culp, David (Frontiers in Microbiology, 2020)
Lack of LrgAB renders cariogenic Streptococcus mutans more sensitive to oxidative stress, as well as limits the capacity of this organism to re-uptake pyruvate upon starvation. This study was aimed at investigating the ecological and metabolic contribution of LrgAB to competitive fitness, using S. mutans strains, that either lack or overexpress lrgAB. These experiments revealed that impaired aerobic growth of the lrgAB mutant can be effectively restored by supplementation of pyruvate, and that perturbated expression of lrgAB significantly affects pyruvate flux and the conversion of pyruvate to acetyl-CoA by the Pdh pathway, verifying that LrgAB is closely linked to pyruvate catabolism. In vitro competition assays revealed that LrgAB plays an important role in S. mutans competition with H2O2-producing S. gordonii, an interaction which can be also modulated by external pyruvate. However, no obvious competitive disadvantage was observed against S. gordonii by either the S. mutans lrgAB mutant or lrgAB overexpression strain in vivo using a mouse caries model. Organic acid analysis of mouse dental biofilms revealed that metabolites produced by the host and/or dental plaque microbiota could complement the deficiency of a lrgAB mutant, and favored S. mutans establishment compared to S. gordonii. Collectively, these results reinforce the importance of the oral microbiota and the metabolic environment in the oral cavity battleground, and highlight that pyruvate uptake through LrgAB may be crucial for interspecies competition that drives niche occupancy.